2013
DOI: 10.1042/bsr20130054
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNAs and their implications in cancer epigenetics

Abstract: LncRNAs (long non-coding RNAs) have emerged as key molecular players in the regulation of gene expression in different biological processes. Their involvement in epigenetic processes includes the recruitment of histone-modifying enzymes and DNA methyltransferases, leading to the establishment of chromatin conformation patterns that ultimately result in the fine control of genes. Some of these genes are related to tumorigenesis and it is well documented that the misregulation of epigenetic marks leads to cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
72
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(74 citation statements)
references
References 77 publications
0
72
0
1
Order By: Relevance
“…Although the specific functions of the large majority of lncRNAs still remain unknown, recent studies have begun to shed light on the critical roles played by these molecules in a variety of cellular processes, including differentiation, development, and tumorigenesis. LncRNAs may play central roles in a wide range of biological processes through interaction with key component proteins and to be involved in gene regulation, including epigenetic regulation, transcription, imprinting, chromosome dosage compensation, nuclear and cytoplasmic trafficking, and mRNA splicing and translation [24,25]. In the present study, we examined the expression of HOTAIR and the association between HOTAIR htSNPs and risk of developing GCA through a case-control approach.…”
Section: Discussionmentioning
confidence: 99%
“…Although the specific functions of the large majority of lncRNAs still remain unknown, recent studies have begun to shed light on the critical roles played by these molecules in a variety of cellular processes, including differentiation, development, and tumorigenesis. LncRNAs may play central roles in a wide range of biological processes through interaction with key component proteins and to be involved in gene regulation, including epigenetic regulation, transcription, imprinting, chromosome dosage compensation, nuclear and cytoplasmic trafficking, and mRNA splicing and translation [24,25]. In the present study, we examined the expression of HOTAIR and the association between HOTAIR htSNPs and risk of developing GCA through a case-control approach.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, mounting evidences have shown that lncRNAs are involved in epigenetic processes [15]. DNA methylation was one of the first epigenetic alterations identified in cancer.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to DNA methylation and histone modifications, epigenetic components, such as nucleosomal positioning, long non-coding RNAs, and RNA interference pathways, change in cancer (Beckedorff et al 2013;Kornienko et al 2013). A detailed description of these changes in cancer is beyond the scope of this review, but the importance of these epigenetic changes has aided the development of new diagnostic and therapeutic modalities as well as understating the cancer biology.…”
Section: Epigenetic Changes In Cancermentioning
confidence: 96%